MODERN METHODS OF TEACHING ENGLISH BASED ON ESP (ENGLISH FOR SPECIFIC PURPOSES) - Abdullayeva Sevara Odashaliyevna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  examines  modern  methods  of  teaching  English  for Specific  Purposes  (ESP)  in  higher  and  vocational  education.  It  highlights  the significance of learner-centered instruction, needs analysis, communicative language teaching,  task-based  learning,  project-based  learning,  digital  technologies,  artificial intelligence,  authentic  materials,  and  competency-based  assessment  in  developing learners'  professional  communicative  competence.  The  study  emphasizes  that  ESP enables  students  to  acquire  language  skills  directly  related  to  their  academic  and occupational  fields,  thereby  increasing  their  employability  and  professional effectiveness.